Pharmacist counseling to cardiac patients in Israel prior to discharge from hospital contribute to increasing patient's medication adherence closing gaps and improving outcomes - Bisharat Bishara (Journal of Translational Medicine, 2012)
Abstract Background Medication non adherence is a global epidemic perplexing phenomenon that is eminent, but not insurmountable. Our first objective was to explore whether providing pharmacist's counseling to cardiac patients prior to discharge can increase patient's medication adherence, and our second objective was to assess whether better medication adherence leads to reduction of hospital readmissions. Methods Observational study was conducted among diagnosed cardiac patients using an intervention strategy at discharge from two hospitals in Israel; The Nazareth and the Haemek hospital. 74 patients were recruited between January 2010 and January 2011. Two separate groups were selected; intervention group: 33 patients who prior to discharge received nurse, pharmacist interventions, and control group: 41 patients who had received the nurse and hospital discharge counseling only. Results Regression analysis for examining the first objective reflected significant effect when having a pharmacist interventions, which explains the increasing 11.6% of the variance in medication adherence, [F change (1,73) = 9.43, p < 0.003]. Stepwise regression analysis for examining the second objective demonstrated that the relation between medication adherence and readmissions was insignificant [F (1,73) = 9.43, n.s]. Conclusions While physicians and nurses can have an impact on improving adherence, pharmacists have demonstrated the ability to inform, problem-solve and provide performance support directly to patients.